The Leadership Style and Strategic Approach of PT. Amway Indonesia Top Management in Establishing Two-Way Communication - Riana Nur Wulan; Ahmad Toni (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the leadership style and communication strategies that the top management of PT Amway Indonesia uses to create effective two-way communication between management and the team. Object study is the three main means of communication: One-on-One, Employee Engagement Survey, and Employee Meeting. With a qualitative approach, this research case study reveals that a transformational leadership style balanced with an open communication strategy positively impacts engagement, employee performance, and sales, improving the company's good image as a company that is conducive to work.